Techniques of play therapy - Dawkins, Kevin (New York, NY : Guilford Publications, 1994)
This program training students and clinicians in play therapy techniques, helping parents understand the process of play therapy, and courses on social work with children, social work practice, family therapy, and counseling psychology
Title from title screen
Executive producer, Robert Matloff, Seymour Weingarten ; graphic design, Lee Dawkins
Presenter: Nancy Boyd Webb
Keywords: Play Therapy -- methods; Play therapy; Child; Infant